2012
DOI: 10.4238/2012.november.28.3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression and characterization of a cysteine peptidase from Xanthomonas citri subsp citri

Abstract: ABSTRACT. Xanthomonas citri subsp citri (Xac) is the bacterium responsible for citrus canker disease in citrus plants. The aim of this study was to describe the recombinant expression, purification, and characterization of a cysteine peptidase from Xac strain 306, which is a candidate for involvement in the pathogenicity of this bacterium. The gene was cloned and expressed in Pichia pastoris, and the cysteine peptidase was successfully expressed, secreted, and purified using affinity chromatography with a yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…To verify if the putative genes involved with sulfate or organic sources of sulfate uptake and assimilation were expressed during the bacterium growth in two defined conditions, we performed a RT-PCR analysis from samples obtained from rich medium LB modified and virulence inducing medium XAM1, which final sulfate concentration is 7.8 mM [ 10 , 30 ]. Total RNA samples were extracted from the X. citri cells grown in the different culture media and used for cDNA amplification (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify if the putative genes involved with sulfate or organic sources of sulfate uptake and assimilation were expressed during the bacterium growth in two defined conditions, we performed a RT-PCR analysis from samples obtained from rich medium LB modified and virulence inducing medium XAM1, which final sulfate concentration is 7.8 mM [ 10 , 30 ]. Total RNA samples were extracted from the X. citri cells grown in the different culture media and used for cDNA amplification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The X. citri strain used in this study was grown at 28 °C overnight in Luria-Bertani (LB) modified broth (without NaCl) supplemented with ampicillin (100 μg/ml) at 28 °C at 200 rpm. After the growth period, the cultures were diluted 50 times, washed two times in sterile water and incubated in virulence induction medium to mimic the plant environment, XAM1 [ 10 , 30 ], or LB until the mid end-exponential growth phase. Samples normalized by O.D.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro growth of the samples was monitored after inoculation of 10 6 CFU of X. citri and Xac::nrtT cultures into 50 mL (1 : 100) of LB broth, XAM1 and XAM1 modified media (XAM1a and XAM1b), where XAM1 is 3.0 m m (NH 4 )SO 4 , 16.5 m m KH 2 PO 4 , 30 m m K 2 HPO 4 , 0.85 m m Na 3 C 6 H 5 O 7 , 100 m m MgSO 4 , 0.18% (m/v) fructose, 0.34% (m/v) sucrose, 0.03% (m/v) casamino acids and 0.1% (m/v) BSA 30; in XAM1a 3.0 m m MOPS and 100 m m MgCl 2 replace (NH 4 )SO 4 and MgSO 4 , respectively; and in XAM1b 3.0 m m taurine replaces (NH 4 )SO 4 . Growth was maintained at 30 °C, 250 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
“…This recombinant cathepsin inhibitor (Soares-Costa et al 2002) interfered with the human cathepsins B, K, L and V, as well as the cysteine peptides from plant source papain and baupain (Oliva et al 2004), and the growth of the filamentous fungus Trichoderma reesei (Soares-Costa et al 2002). Currently, there are five recombinant cystatins derived from sugarcane named CaneCPI-1, CaneCPI-2, CaneCPI-3, CaneCPI-4 and CaneCPI-5 (Gianotti et al 2006, Oliveira et al 2011, Soares-Costa et al 2012, Santiago et al 2017. Studies have shown that CaneCPI-4 has reduced invasion of tumour cells in vitro (Gianotti et al 2008), inhibited the development of melanoma in vivo and decreased the angiogenesis process in vitro and in vivo (Oliveira et al 2011).…”
Section: Introductionmentioning
confidence: 99%